Assisting primary care teams and patients in a culturally diverse periphery: impact on medical students’ future career choices - Nosaiba Rayan-Gharra; Lilach Malatskey; Marganit Ofir-Gutler; Rizan Sakhnini; Awni Yousef; Mohammad Khatib; Karl Skorecki; Sivan Spitzer (BMC Medical Education, 2024)
Abstract Background Medical students can assist in reducing healthcare disparities and promote health equity by engaging with rural communities and gaining insights into their unique healthcare needs. A two-arm student-delivered program was designed and implemented during COVID-19 in a social-geographic peripheral area to assist clinics with complex chronic and/or socially disadvantaged patients and improve preventive behavior in townships through home visits delivering community kits. Methods We conducted a pre-post design study which included weekly structured medical student reports and monthly structured telephone interviews with clinic directors and municipal partners. Students completed pre-post program survey on their knowledge, skills, and capabilities to address chronic patients from diverse cultural backgrounds (n = 73). The Wilcoxon-Signed-Rank test for related samples was used to determine differences. Results Following the program, the knowledge and awareness levels of students about working in the community (P < 0.001) and their knowledge of common chronic diseases were significantly improved (Mean Difference (MD) = 0.31; p < 0.001). The program significantly increased students’ interest to integrate into community care alongside a hospital (P = 0.012). Thematic analysis of student reports revealed improved insight into the role of primary care. Clinic directors (90%) were highly satisfied and reported that students became an integral part of the clinics’ teams. Conclusions Integrating medical students into the community through primary-care clinics and home visits in diverse communities, exposed students to the interwoven effect of clinical and social determinants on health and improve their knowledge of common chronic diseases. Participation in the program encouraged students to consider a career in community care.